Tourism Development During the Pandemic of Coronavirus (COVID-19): Evidence From Iran - Hallaj, Zeynab; Bijani, Masoud; Abbasi, Enayat; Valizadeh, Naser; Mohammadi, Maryam (Frontiers in Public Health, 2022)
The coronavirus (COVID-19) epidemic has created a great deal of fear and uncertainty about health, economy, and social life. Therefore, the health, social, and economic impacts of COVID-19 are of great importance. In prone rural communities, tourism industry can contribute to the sustainable economy and social development of the villagers, and as a dynamic economic sector, cause economic, social, cultural, and environmental changes. In this regard, the purpose of this inquiry was to develop tourism during the coronavirus pandemic using the social exchange theory (SET). The present study is a descriptive, correlational and causal inquiry that is conducted using survey technique. The statistical population included tourists visiting Sistan region around Hamoun Wetland in eastern Iran (N = 850). In the sampling process, 266 tourists were selected as a sample using random sampling strategy. The study instrument was a researcher-made questionnaire, whose validity was confirmed by a panel of subjectivists and its reliability was approved by a pilot study and Cronbach's alpha coefficients (0.87≥ α ≥ 0.71). Based on SET, the proposed causal model was able to explain about 56% (R2Adj = 0.562) of the variance changes in tourism development during the COVID-19 epidemic.